Ventilation effectiveness in underground car parks - Zuraidi Mohamed Dahlan. (2008)
Ventilation requirements in terms of the air change rate in car parks have been specified in many countries with a common goal of maintaining pollutant concentration within an acceptable level for human health. These codes do also provide some guide as to the location of openings in the walls for natural ventilation or the location of the supply and exhaust ports in a mechanical ventilation system.